Induction of wheat resistance by Streptomyces sp. HU2014 strain - Zhu, Hongxia; Rozhkova, T. (Quarantine and plant protection, 2023)
Goal. To determine changes in the activity of enzymes (POD, PAL and GLU) of Triticum aestivum when Streptomyces sp. HU2014, Rhizoctonia cerealis G11 are introduced into the soil and their simultaneous application. Methods. Laboratory: cultivation of microorganisms and wheat plants, introduction of actinomycetes and fungus into the soil. Physico-chemical: POD, PAL and GLU colorimetry. Analytical and mathematical: analysis of the obtained results and their statistical comparison. Results. Changes in the activity of enzymes (POD, PAL and GLU) were noted in the leaves of wheat plants at different time intervals, compared to the control variant. The change manifested mostly in the increase of their activity. The maximum amount of enzyme activity was noted on one variety ZM22: on the third day of POD when inoculated according to the CKP scheme (15762.69 U/g) and GLU when introducing the microorganism into the soil according to the PF3 scheme (28.45 U/g); on the fourth day of the PAL study according to the treatment scheme PF3 (29.37 U/g). The induction of resistance was also determined by the wheat variety. Conclusions. The activity of POD, PAL and GLU was determined by the plant treatment scheme, time period and genotype of the crop. In most cases, during soil treatment with microorganisms, the activity of all three studied enzymes from the leaves of three varieties of wheat increased in different periods of time, compared to the control. The activity of PAL enzyme increased to the greatest extent. It was established that the activity of the POD enzyme was mostly determined by R. cerealis and the dual use of microorganisms, the PAL enzyme by a strain of Streptomyces sp. HU2014, and the GLU enzyme — by inoculation with a phytopathogen and introduction of actinomycetes. That is, changes in the activity of all three enzymes were mostly determined by the strain of Streptomyces sp. HU2014. At the same time, it was shown that R. cerealis G11 mainly induced the defense system of AK58 and ZM22 varieties, and HU2014 induced the defense of BN307.